Acetic Acid Production and Purification: Critical Review Towards Process Intensification. Issue 1 (2nd January 2017) - Pal, Parimal; Nayak, Jayato
Abstract : The 1980–2015 literature has been critically reviewed to examine how acetic acid manufacturing practice has progressed over these 35 years and whether this important organic acid manufacturing sector is on the right track to ensure sustainable business. Amidst growing environmental awareness and emerging regulations all over the world, a paradigm shift in production strategy in favor of green processes appears imminent. Literature reveals that despite huge worldwide demand, conventional manufacturing practices still largely revolve around multi-step and multi-phase unit operations that fail to ensure clean production environment. Production process is still dominated by a chemical synthesis route where multiple traditional unit operations like distillation, evaporation, absorption, filtration, crystallization, acid and alkali treatments are required involving huge energy, material, manpower, and capital consumption. On the other hand, prospects for process intensification through adoption of membrane technology in downstream separation and purification appear to have brightened. Emergence of tailor-made and highly selective membranes in fouling free modules has opened up new avenues towards green production that has the potential of ensuring sustainable business. This article directs further research towards process intensification.